Improving Regional Welfare Through Stakeholder Management: Social Network Analysis (SNA) in the Management of the Floating Market - Cavin Ornando Simorangkir; Fitri Yuniawati; Monica Adellia; Affra Nabilla; Dewi Purba (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2024)
The Floating Market holds significant potential to attract tourists, making it essential to integrate a welfare-oriented approach into its management to ensure contributions to regional development. Effective governance and collaboration among stakeholders, including local governments and non-governmental actors, are crucial for balancing tourism growth with sustainability. This study explores the roles of stakeholders in managing Floating Market resources, identifies key challenges, and offers insights for promoting local engagement and enhancing regional welfare through targeted policies. Using a descriptive qualitative approach, the research employs purposive sampling to conduct in-depth interviews with key stakeholders, including Floating Market management, workers, local residents, and representatives from the West Bandung Regency (KBB) Tourism and Culture Agency. Data analysis, using Social Network Analysis (SNA) and stakeholder mapping, identifies roles, relationships, and influence within tourism management. The results highlight critical issues affecting regional welfare, such as a lack of transparency in recruitment, limited training opportunities for workers, low wages, and environmental challenges like traffic congestion and waste management. The study suggests strategies to address these issues, including creating inclusive recruitment processes, implementing routine professional development programs, establishing fair wages, integrating health and employment insurance, improving infrastructure, and promoting sustainable practices. Another key strategy is to enhance the use of local products in the market, supporting local agriculture. Additionally, fostering open communication between management and locals is vital to ensure equitable distribution of tourism benefits. Effective stakeholder management can enhance the socio-economic impacts of tourism, benefiting both the Floating Market and the broader West Bandung Regency.